Attitude Control and Simulation of a low Orbit Nanosatellite - Camilo, Vitor Mendes; Pazelli, Tatiana F. P. A. T. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2024)
Nanosatellites have been objects of research and application in recent years due to the accessibility promoted by the standardization of components and structures. The various applications of this type of device require well-determined and controlled behavior. In this work, a nanosatellite simulation platform provided by Matlab/Simulink was extended and applied to validate closed-loop attitude control techniques using a set of reaction wheels as actuators for low-orbit operation. The attitude of a small satellite was controlled from an unfavorable initial condition, in a movement known as detumbling. The implemented PID controller showed good results in regulating the satellite's orientation angles in low orbit, correcting and maintaining its pointing towards the Earth, without saturating the set of reaction wheels.